Global prevalence, treatment and outcome of tuberculosis and COVID-19 coinfection: a systematic review and meta-analysis (from November 2019 to March 2021) - Qiang Sun; Hui Li; Jie Zhao; Xiaolin Wei; Quan Wang; Shasha Guo; Quanfang Dong; Ning Xu (BMJ Open)
Introduction The COVID-19 outbreak poses a significant threat to the patients with tuberculosis (TB). TB and COVID-19 (TB–COVID) coinfection means the disease caused by both Mycobacterium tuberculosis and SARS-CoV-2 infection. Currently, the prevalence status, treatment and outcomes of the coinfection are poorly characterised. We aimed to systematically review the evidence on this topic and provide comprehensive information to guide the control and treatment of TB–COVID coinfection.Methods An extensive screening was conducted using six electronic databases to search eligible studies from 1 November 2019 to 19 March 2021. Prevalence rate, treatment and outcomes of TB–COVID coinfection were extracted. Random-effects models were used to calculate mean fatality rates of coinfection with 95% CIs. The risks of bias were assessed with the Joanna Briggs Institute (JBI) Critical Appraisal Checklist for Study Reporting Prevalence Data and JBI Critical Appraisal Checklist for Case Report. A meta-analysis was conducted for subgroups on in-hospital fatality rate.Results Forty-two studies were included into the analysis (35 case reports and 7 retrospective cohort studies). Nineteen countries reported coinfected patients, including high and low TB prevalence countries. The only study revealing prevalence rate came from West Cape Province, South Africa (people aged above 20 years, 0.04% until 1 June 2020 and 0.06% until 9 June 2020). The treatment regimens for coinfected patients were highly heterogeneous. The mean overall and in-hospital fatality rates of coinfection were 13.9% (95% CI: 1.6% to 26.2%) and 17.5% (95% CI: 8.9% to 26.0%). The mean in-hospital fatality rates for high-income countries (Italy and Argentina) and low/middle-income countries (LMICs) (India, Philippines, South Africa) were 6.5% (95% CI: −0.8% to ~13.9%) and 22.5% (95% CI: 19.0% to ~26.0%).Conclusion TB–COVID coinfection is common globally, and the coinfected patients suffer from higher fatality risk than patients with normal COVID-19. Outcomes shared significant differences between high-income countries and LMICs.PROSPERO registration number CRD42021253660.